Lysobacter changpingensis sp. nov., a novel species of the genus Lysobacter isolated from a rhizosphere soil of strawberry in China - Niu, Bang-Yan; Ren, Dong-Jun; Zhang, Fang-Bo; Zhu, Hong-Tu; Wei, Hai-Lei; Ma, Ming-Chao; Gao, Miao (Folia microbiologica, 2023)
In the present work, we characterized in detail strain CM-3-T8T, which was isolated from the rhizosphere soil of strawberries in Beijing, China, in order to elucidate its taxonomic position. Cells of strain CM-3-T8T were Gram-negative, non-spore-forming, aerobic, short rod. Growth occurred at 25-37 °C, pH 5.0-10.0, and in the presence of 0-8% (w/v) NaCl. Phylogenetic analysis based on 16S rRNA gene sequences revealed that strain CM-3-T8T formed a stable clade with Lysobacter soli DCY21T and Lysobacter panacisoli CJ29T, with the 16S rRNA gene sequence similarities of 98.91% and 98.50%. The average nucleotide identity and digital DNA-DNA hybridization values between strain SG-8 T and the two reference type strains listed above were 76.3%, 79.6%, and 34.3%, 27%, respectively. The DNA G + C content was 68.4% (mol/mol). The major cellular fatty acids were comprised of C15:0 iso (36.15%), C17:0 iso (8.40%), and C11:0 iso 3OH (8.28%). The major quinone system was ubiquinone Q-8. The major polar lipids were phosphatidylethanolamine (PE), phosphatidylethanolamine (PME), diphosphatidylglycerol (DPG), and aminophospholipid (APL). On the basis of phenotypic, genotypic, and phylogenetic evidence, strain CM-3-T8T (= ACCC 61714 T = JCM 34576 T) represents a new species within the genus Lysobacter, for which the name Lysobacter changpingensis sp. nov. is proposed.
Keywords: New species; mastné kyseliny; Lysobacter; jahodník; Fatty Acids; China; DNA bakterií; Rhizosphere; RNA, Ribosomal, 16S; Lysobacter sp.; DNA, Bacterial; fosfolipidy; rhizosféra; Phylogeny; fosfatidylethanolaminy; Phospholipids; Čína; Bacterial Typing Techniques; Sequence Analysis, DNA; techniky typizace bakterií; Phosphatidylethanolamines; Fragaria; sekvenční analýza DNA; Soil; půda; fylogeneze; Phenotypic; Rhizosphere microbiota; RNA ribozomální 16S